2016
DOI: 10.1103/physrevb.93.205410
|View full text |Cite
|
Sign up to set email alerts
|

Nanometer-scale monitoring of quantum-confined Stark effect and emission efficiency droop in multiple GaN/AlN quantum disks in nanowires

Abstract: We report on a detailed study of the intensity dependent optical properties of individual GaN/AlN Quantum Disks (QDisks) embedded into GaN nanowires (NW). The structural and optical properties of the QDisks were probed by high spatial resolution cathodoluminescence (CL) in a scanning transmission electron microscope (STEM). By exciting the QDisks with a nanometric electron beam at currents spanning over 3 orders of magnitude, strong non-linearities (energy shifts) in the light emission are observed. In particu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 74 publications
(98 reference statements)
2
13
0
Order By: Relevance
“…The emission energy shift with intensity, shown in Figure 4a, is in good agreement with previous work which also indicated about a 1 eV shift with current (Carnevale et al, 2013). In other work, it has been shown that blue shifts are also observed for thicker GaN/AlN Qdisks (>4 nm), consistent with what is shown here, and that for thinner Qdisks (<3 nm), the blue shift is near absent, interpreted as being due to negligible QCSE at such length scales (Zagonel et al, 2016).
Figure 4 a: Comparing peak wavelength of cathodoluminescence (CL) emission as a function of CL intensity when scanning regions of the nanowire above and below the GaN quantum well (QW) for GaN×1.
…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The emission energy shift with intensity, shown in Figure 4a, is in good agreement with previous work which also indicated about a 1 eV shift with current (Carnevale et al, 2013). In other work, it has been shown that blue shifts are also observed for thicker GaN/AlN Qdisks (>4 nm), consistent with what is shown here, and that for thinner Qdisks (<3 nm), the blue shift is near absent, interpreted as being due to negligible QCSE at such length scales (Zagonel et al, 2016).
Figure 4 a: Comparing peak wavelength of cathodoluminescence (CL) emission as a function of CL intensity when scanning regions of the nanowire above and below the GaN quantum well (QW) for GaN×1.
…”
Section: Discussionsupporting
confidence: 91%
“…Taken at face value, this observation implies that although there are more carriers present for screening, the polarization distortion increases with increased carrier injection, which cannot be explained by the simple one-dimensional (1D) band edge diagram. It is also worth noting that red shifting was not observed in the work by Zagonel et al, regardless of size of the Qdisk (Zagonel et al, 2016). Although polarization effects are only expected along the z -direction ( c -axis), the three-dimensional (3D) nature of the heterostructures can also generate radial polarization effects, even along intrinsically nonpolar directions within the basal plane of wurtzite.…”
Section: Discussionmentioning
confidence: 80%
“…During such a long lifetime duration, the QWs are likely to be excited several times, leading to a charge carrier accumulation screening the internal field, thus reducing the lifetime. 18 Several lifetimes can thus be observed, leading to a non-monoexponential decay. Because of the small thicknesses of the QWs explored here, 18 a few angstroms, the QCSE effect is too weak to induce such large lifetimes, as is obvious in Figure 3 and confirmed by the fact that the emission energies are always larger than or only slightly below the GaN bulk band gap energy.…”
mentioning
confidence: 99%
“…18 Several lifetimes can thus be observed, leading to a non-monoexponential decay. Because of the small thicknesses of the QWs explored here, 18 a few angstroms, the QCSE effect is too weak to induce such large lifetimes, as is obvious in Figure 3 and confirmed by the fact that the emission energies are always larger than or only slightly below the GaN bulk band gap energy. Nevertheless, such extreme cases are usually handled in the case of TR-μPL measurements through multiexponential fitting procedures.…”
mentioning
confidence: 99%
“…31,32 CL-STEM on the other hand is suitable for probing the nanoscale optical properties of nanowires because of the small interaction volume and high resolution resulting from the high acceleration voltage used. [33][34][35] Through utilizing CL-STEM, it is possible to simultaneously retrieve both the optical and structural features of the nanowires while at the same time utilizing a high-angle annular dark field (HAADF), providing a thorough understanding of how structural features and luminescence properties of nanowires affect each other. This capability has been demonstrated to investigate the nanoscale optical properties of nanowire heterostructures, 22,36 with features as small as nanometer-sized clusters.…”
mentioning
confidence: 99%